Effects of a novel combination of magnesium, tryptophan, resveratrol, and saffron on oxidative stress, prostaglandin F2α, and intracellular Ca2+ levels in an in-vitro model of myometrium - BATTAGLIA, Stefania; COZZI, Marco; RANIERI, Francesca R.; GAIO, Elisa; BENETTI, Federico; CURTI, Valeria (Minerva Biotechnology and Biomolecular Research, 2023)
BACKGROUND: Dysmenorrhea and premenstrual syndrome (PMS) are the main disorders related to the menstrual cycle. The prevailing symptoms of dysmenorrhea are painful cyclic cramps in the lower abdomen, while PMS is accompanied by a wide and varied set of symptoms that includes both physical and psychological aspects. These disorders are characterized by oxidative stress, increased production of prostaglandin F2α (PGF2α), and intracellular calcium concentration ([Ca2+]i) in myometrium. Currently, the main pharmacological therapies involve the use of NSAIDs and combined hormonal contraceptives, even if both approaches may have some limitations. Recent scientific evidence supports the use of food supplements for symptom prevention and management, also in association with conventional therapies. The study aimed to investigate the in-vitro effect of a novel combination of active substances (mix), composing the food supplement Miledix® (Kolinpharma S.p.A., Lainate, Milan, Italy) on: 1) antioxidant activity; 2) variation of PGF2α levels; and 3) variation of [Ca2+]i induced by PGF2α. METHODS: We used a primary human cell line of uterine smooth muscle. Cell viability was assessed by MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] test. Oxidative stress was investigated with glutathione assay and dichlorodihydrofluorescein diacetate assay. PGF2α levels were assessed by ELISA while [Ca2+]i by fluorometric test. RESULTS: Results show that the mix determines an increase in the Reduced Glutathione/Oxidized Glutathione Ratio, while it decreases reactive oxygen species levels, the expression of PGF2α, and [Ca2+]i induced by prostaglandin. CONCLUSIONS: Under these experimental conditions, the mix was able to act on the molecular mechanisms underlying the onset of cycle disorders, such as oxidative stress, the production of PGF2α, and the accumulation of [Ca2+]i.